"In the lungs and out by the mouth": the intrauterine device in Singapore, 1965-1986 - Ng, Nicole Shi Min (Nanyang Technological University, 2024)
This thesis examines the usage of and narratives surrounding the intrauterine device (IUD) within Singapore from the years 1965 to 1986, when it pursued an anti-natalist family planning policy aimed at reducing the birth rate. It explores the significant global and local events that have impacted IUD usage in Singapore. It is demonstrated that the IUD was initially pushed as the main contraceptive method to be utilised in Singapore due to the influence of neo-Malthusianism from the Western world, before a rejection of the IUD by local women necessitated a change in family planning policies. However, despite the early rejection and low popularity of the IUD, it has influenced family planning policies in other ways. This thesis argues that while the IUD was initially accorded significant value and heavily pushed by the government, subsequent fears over women’s health and the negative public image of the IUD led to decreasing emphasis on the IUD as a method of contraception in Singapore from 1965 to 1986.